Law Enforcement in Cases of Maltreatment of Minors According to Positive Law and Islamic Law Case Study of Decision Number 4/Pid.Sus/2022/Pn Tte, Decision Number 39/Pid.Sus-Anak/2021/Pn Mks, and Decision Number 12/Pid.Sus/2022/Pn Soe - Okta Thaharah Susanto; Yusup Hidayat; Aris Machmud (Journal of Law, Politic and Humanities, 2025)
Law enforcement against child abuse crimes in Indonesia still faces various challenges, although the Child Protection Law has provided a strong legal basis. This study aims to analyze the application of law in cases of child abuse based on positive law and Islamic law, and to assess the influence of social and cultural factors that influence the law enforcement process. The research method used is a normative approach with a literature study, in which three court decisions are analyzed as case studies, namely Decision Number 4 / Pid.Sus / 2022 / PN Tte, Decision Number 39 / Pid.Sus-Anak / 2021 / PN Mks, and Decision Number 12 / Pid.Sus / 2022 / PN Soe. The results of the study show variations in the application of sanctions, especially in cases involving child perpetrators and the influence of a culture that is permissive of violence. These factors show inconsistencies in law enforcement that can impact public perceptions of justice. Islamic law offers an alternative approach through the concept of restorative justice, which emphasizes victim recovery and perpetrator rehabilitation, and has the potential to be integrated into the national legal system to strengthen the effectiveness of child protection. This study recommends improving rehabilitation programs for child perpetrators, educating the public to change permissive attitudes towards child abuse, and adopting Islamic legal principles that are oriented towards recovery in the national legal system. These recommendations are expected to strengthen legal protection for children in Indonesia and support the creation of a legal system that is more just and responsive to the rights of children as victims of violence